2015
DOI: 10.1002/ece3.1772
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of bark beetle adaptation to a fungal symbiont

Abstract: The importance of symbiotic microbes to insects cannot be overstated; however, we have a poor understanding of the evolutionary processes that shape most insect–microbe interactions. Many bark beetle (Coleoptera: Curculionidae, Scolytinae) species are involved in what have been described as obligate mutualisms with symbiotic fungi. Beetles benefit through supplementing their nutrient‐poor diet with fungi and the fungi benefit through gaining transportation to resources. However, only a few beetle–fungal symbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 45 publications
0
30
0
2
Order By: Relevance
“…sp. B and C. brevicomi were acquired from mycangia of D. brevicomis (Bracewell and Six, ) (Table ). Ophiostoma minus was isolated directly from the tree cores collected in this study.…”
Section: Methodsmentioning
confidence: 99%
“…sp. B and C. brevicomi were acquired from mycangia of D. brevicomis (Bracewell and Six, ) (Table ). Ophiostoma minus was isolated directly from the tree cores collected in this study.…”
Section: Methodsmentioning
confidence: 99%
“…For example, western pine beetle (Dendroctonus brevicomis) is known to exhibit strong fidelity to one of two inherited mycangial fungal symbionts, Ceratocystiopsis brevicomi and/or Entomocorticum sp. B, which is suggestive of coevolution of the beetle with their associated fungi [35,41]. Other fungi associated with the western pine beetle, such as O. minus or O. ips, are not carried in the mycangia and are antagonistic to the beetle.…”
Section: Insect Physiology and Ecologymentioning
confidence: 99%
“…A (basidiomycete) [4,36], and the mountain pine beetle is associated with three Ophiostomatoid mycangial fungi-Ophiostoma montium [37], Grosmania clavigera, and Leptographium longiclavatum [38,39] but are also known to harbor Ceratocystiopsis and Entomocorticium [40]. However, only one fungal species exists within an individual beetle's mycangium and is inherited from the original parental pair [2,41]. Other bark beetles such as (most) Ips spp.…”
Section: Bark Beetle-fungal Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this experiment showed that beetle fitness did not vary when grown together with natal (isolated from same beetle population used in the study) and non-natal (genetically distinct isolate from geographically distinct beetle population) fungal isolates. Interestingly, emerging adults incorporated only the natal isolate into the mycangium and avoided the non-natal isolate (Bracewell and Six 2015). …”
Section: Fungal Associates Play Important Roles In Bark Beetle Life Hmentioning
confidence: 99%